Effect of combined platinum and electron on the temperature dependence of forward voltage in fast recovery diode - 贾云鹏 赵豹 杨霏 吴郁 周璇 李哲 谭健 (Chinese physics B, 2015)
The temperature dependences of forward voltage drop（VF） of the fast recovery diodes（FRDs） are remarkably influenced by different lifetime controlled treatments. In this paper the results of an experimental study are presented, which are the lifetime controls of platinum treatment, electron irradiation treatment, and the combined treatment of the above ones.Based on deep level transient spectroscopy（DLTS） measurements, a new level E6（EC-0.376 e V） is found in the combined lifetime treated（CLT） sample, which is different from the levels of the individual platinum and electron irradiation ones. Comparing the tested VFresults of CLT samples with the others, the level E6 is responsible for the degradation of temperature dependence of the forward voltage drop in the FRD.